2005
DOI: 10.1177/0091270005277936
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Acting Octreotide and Prolonged‐Release Lanreotide Formulations Have Different Pharmacokinetic Profiles

Abstract: Single-dose pharmacokinetic (PK) profiles and multiple-dose PK modeling were compared for long-acting octreotide (20 or 60 mg) and prolonged-release lanreotide (90 or 120 mg) over 91 days; steady-state profiles were simulated. All treatments were well tolerated. Octreotide 20-mg profile showed increased concentration on day 1, lag from days 2 to 6, then prolonged plateau phase (days 11-41); 60-mg PK was dose proportional. Lanreotide 90-mg profile showed C(max) on day 1 then elimination (apparent t1/2 25.5 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 41 publications
2
83
1
1
Order By: Relevance
“…The dissociation between receptor expression and internalization might be explained by another animal study, in which octreotide medication induced rapid SSTR subtype 2 internalization within 2.5 min in vivo, followed by recovery of receptor expression within 24 h (17). With the long-acting octreotide, the serum concentration remains quite stable over 28 d (18), as might be expected to result in concomitant receptor internalization and overexpression. This stability, however, need not also hold true for other somatostatin analogs such as lanreotide, for which the serum concentration decreases over time (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dissociation between receptor expression and internalization might be explained by another animal study, in which octreotide medication induced rapid SSTR subtype 2 internalization within 2.5 min in vivo, followed by recovery of receptor expression within 24 h (17). With the long-acting octreotide, the serum concentration remains quite stable over 28 d (18), as might be expected to result in concomitant receptor internalization and overexpression. This stability, however, need not also hold true for other somatostatin analogs such as lanreotide, for which the serum concentration decreases over time (18).…”
Section: Discussionmentioning
confidence: 99%
“…With the long-acting octreotide, the serum concentration remains quite stable over 28 d (18), as might be expected to result in concomitant receptor internalization and overexpression. This stability, however, need not also hold true for other somatostatin analogs such as lanreotide, for which the serum concentration decreases over time (18).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly octreotide but also lanreotide has been proven to have a long biological half-life when given in slow-release formulas, and can be detected in circulation many weeks after injection (20,21). A phase I study demonstrated that the concentration of octreotide LAR decreases slowly to immeasurable values in the first 11 weeks after a single injection (22). A clinical study of SSA withdrawal has demonstrated suppressed hormone levels for several months in some patients (23).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Stable compound such as OCT LAR is now available for a convenient monthly injection and improves patient compliance. Prolonged drug release of OCT LAR is achieved by encapsulation in microspheres composed of a tumor [10]. Fluctuation of blood drug level may be seen in the initial 7-14 days.…”
Section: Discussionmentioning
confidence: 99%